Power of Notion: Rules, Practices and Self-evaluation of the Poor Relief of the Reformed Church in Late Eighteenth-century Rotterdam - Onishi, Yoshiyuki (TSEG - The Low Countries Journal of Social and Economic History, 2016)
Though Dutch poor relief has been appreciated by historians for the financial stability and generous assistance given to the poor, this paper examines the harsh reality to poor relief in the late eighteenth-century Netherlands. Using archival material from the Reformed Diaconate in Rotterdam, this paper deals with regulations for poor relief, compliance with them and its achievements and attempts at reform to show that not only strangers but also residents were often unable to receive (additional) alms due to strict regulations. This work also demonstrates that the notion of ‘overly generous poor relief’ and ‘lazy poor’ shared by the Deaconate and city authorities led to the tightening of the rules for almsgiving and adherence to them.